1975
DOI: 10.1111/j.1365-2133.1975.tb03084.x
|View full text |Cite
|
Sign up to set email alerts
|

Mites in the environment of cases of Norwegian scabies

Abstract: Three cases of Norwegian Scabies diagnosed in Glasgow hospitals within 1 year each caused wide-spread outbreaks of papular eruptions amongst the patients and staff, followed later by a few cases of classical scabies. Symptoms and timing suggested that these infections were caused by immature mites derived by personal contact and possibly by contact with infected cuticular fragments which were abundant in the environment of the three patients. To control a ward epidemic, isolation of the Norwegian scabietic sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…[3] A population density of 6,312 mites/g was demonstrated in the dust from bed linen of such a patient. [4] Crusted scabies occurs with increased frequency among patients with leukemia, HIV infection, Down’s syndrome, lepromatous leprosy and diabetes. [45]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] A population density of 6,312 mites/g was demonstrated in the dust from bed linen of such a patient. [4] Crusted scabies occurs with increased frequency among patients with leukemia, HIV infection, Down’s syndrome, lepromatous leprosy and diabetes. [45]…”
Section: Discussionmentioning
confidence: 99%
“…[4] Crusted scabies occurs with increased frequency among patients with leukemia, HIV infection, Down’s syndrome, lepromatous leprosy and diabetes. [45]…”
Section: Discussionmentioning
confidence: 99%
“…crotamiton and benzyl benzoate weekly, in combination with the administration of lindane to hyperkeratotic crusts daily. 20–22 Correct application must be achieved, including the subungual areas and up to the edges of the lower body orifices. Additionally, subungual areas are often filled with hyperkeratotic crusts which require daily scrubbing with topical antiscabiotics in combination with nail trimming.…”
Section: Discussionmentioning
confidence: 99%
“…Today the most accepted opinion is that Norwegian scabies is an infestation with the Sarcoptes scabiei var hominis. This is proved by many reports of epidemics of typical scabies in other patients or in medical persons [1,3,7,9], D egos' [4] opinion is that this form of scabies usually occurs in old people, mainly in male mongols, with absence of or reduced pruritus [6,7,10]. Nutritional deficiency seems to be a possible factor in some cases and severe systemic diseases as leukemia, diabetes [4] and reticuloendotheliosis [2].…”
Section: Discussionmentioning
confidence: 99%
“…The mites promote keratotic reaction of the skin and on the other hand keratotic masses allow an undis turbed procreation. Some authors have found in floor dust of their patients' homes 840 mites/g, and on the chairs 333 mites/g [3].…”
Section: Discussionmentioning
confidence: 99%